The effect of the marketing mix on purchase decisions and customer satisfaction - Angelika Rouli Sinaga; Nur Elfi Husda (Journal of Community Service and Empowerment, 2023)
Purchasing decisions and customer satisfaction are what determine marketing. This study aimed to analyze the effect of marketing mix variables of price, place, and promotion on purchase decisions and customer satisfaction at SDS Nusantara of Batam City. The research method used was quantitative method with data collected using questionnaires distributed directly to 150 respondents and using accidental sampling. The data processing analysis used in this research was SemPLS 3.2.9 application. The results of this study found that the price, place and promotion variables had a positive and significant effect, then the price, place and promotion variables also had significant and positive effect on customer satisfaction, finally the purchase decision had a positive and significant effect on customer satisfaction.